2020
DOI: 10.1101/2020.12.11.421859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Annexin A1 tripeptide mimetic increases sirtuin-3 to augment mitochondrial function and limit ischemic kidney injury

Abstract: BackgroundAcute kidney injury (AKI) is one of the most common organ failures following surgery. We have developed a tripeptide mimetic (ANXA1sp) of the parent annexin A1 molecule that shows promise as an organ protectant limiting cellular stress; however, its potential as a kidney protective agent remains unexplored, and its mechanism of action is poorly understood. Our hypothesis was that ANXA1sp would limit kidney injury and improve mitochondrial function following surgical ischemic kidney injury.MethodsIn b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Previous studies demonstrated that oxidative stress evoked by TBI boosts neuroin ammation and contributes to neuronal degeneration and cell death in the brain after injury. AnxA1 has not only been con rmed to exert neurological bene t, but also has been demonstrated to correlate with oxidative stress in several disease conditions, including a chronic obstructive pulmonary disease in vitro model induced by cigarette smoke extract (Yu and Zhang, 2022) and ischemic kidney injury (Suliman et al, 2021). Thus we set out to investigate the effect of AnxA1 on expression of oxidative stress factors in DAI.…”
Section: Annexin A1 De Ciency Signi Cantly Increased the Apoptotic In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that oxidative stress evoked by TBI boosts neuroin ammation and contributes to neuronal degeneration and cell death in the brain after injury. AnxA1 has not only been con rmed to exert neurological bene t, but also has been demonstrated to correlate with oxidative stress in several disease conditions, including a chronic obstructive pulmonary disease in vitro model induced by cigarette smoke extract (Yu and Zhang, 2022) and ischemic kidney injury (Suliman et al, 2021). Thus we set out to investigate the effect of AnxA1 on expression of oxidative stress factors in DAI.…”
Section: Annexin A1 De Ciency Signi Cantly Increased the Apoptotic In...mentioning
confidence: 99%
“…In addition, AnxA1 peptide Ac2-26 signi cantly suppressed the activity of NADPH oxidase and malondialdehyde to decrease oxidative stress, lung injury and epithelium apoptosis in acute respiratory distress syndrome rats (Ju et al, 2023). Besides, in the kidney following ischemic injury, AnxA1 limited ROS production and increased antioxidant enzymes to abrogate oxidative stress and attenuate tubular cell death, which nally preserves the kidney against the ischemia (Suliman et al, 2021). Furthermore, Ac2-26 signi cantly ameliorated neuronal apoptosis, reduced the volume of cerebral infarct and improved the neurological function of mice on cerebral I/R (ischemic/reperfusion) injury (Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Ischemia reperfusion model. Ischemia-reperfusion was performed as previously described via unilateral vascular clamping and contralateral nephrectomy (Suliman et al, 2021). Briefly, mice were anesthetized with ketamine/xylazine.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Renoprotective effects of AnxA1 have been demonstrated for a variety of not primarily immune-mediated conditions including diabetic nephropathy (Wu et al, 2021), ischemia/ reperfusion injury (Facio et al, 2011;Suliman et al, 2021) and calcineurin inhibitor toxicity (Araujo et al, 2010;Araujo et al, 2012). Protective mechanisms include antiinflammatory and antifibrotic effects via formyl peptide receptor 2 signaling, alteration of MAP kinase signaling and inhibition of TGF-β and NF-kB (Neymeyer et al, 2015;Purvis et al, 2018;Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%